The Impact of CEO and CFO Gender on Family Firm Performance - Dezfouli, Kaveh Moradi; Ravi, Rahul (Journal of Applied Business and Economics, 2024)
This study examines the impact of CEO and CFO gender on firm performance, with a focus on family firms. Family firms focus on strategic decision-making with a tendency to pass the firm to the next generations which includes the appointment of top executives. Since family firms are more likely to appoint a family member as CEO or CFO, common gender-based discriminatory practices play a lesser role in these decisions. Our results indicate that non-family firms with female CEOs or CFOs outperform those with male CEOs or CFOs. However, in contrast to non-family firms, the performance of family firms does not vary based on the gender of the CEO or CFO. This underscores the various discriminatory practices women face throughout the entirety of their careers, as female executives must demonstrate superior abilities to “shatter the glass ceiling” and attain top executive positions. Our study highlights the importance of addressing gender-based discriminatory practices at various stages of women's careers, rather than focusing solely on their tenure as top executives.